A poesia como rasura em Carlfriedrich Claus e Ana Hatherly - Amaral, André Luiz Do (Universidade de São Paulo/Faculdade de Filosofia, Letras e Ciências Humanas/Programa de Pós-Graduação em Língua e Literatura Alemã, 2018)
Abstract Carlfriedrich Claus and Ana Hatherly visual works are outside what is conventionally named poetry. A poetry without words remains impossible for the defenders of writing as a logocentric practice. Therefore, the authors studied here invite a deviant reading of the contemporary poetry. They assume contemporary poetry tends toward iconicity and even the complete illegibility as a way of aesthetically apprehending the chaotic world. Since they neither follow the same rules of the traditional lyric, nor can they be read from those regulating principles, these poets deliberately obliterate texts implicate an unequivocal transformation of the creative and reading methods, notwithstanding the resistance from some lines of criticism.

Resumo As obras visuais de Carlfriedrich Claus e de Ana Hatherly se localizam fora daquilo que se convencionou chamar de poesia. Uma poesia sem palavras resta como impossibilidade para os defensores da prática logocêntrica da escrita. Os autores aqui estudados suscitam, portanto, uma leitura desviante da atividade poética contemporânea. Eles defendem a hipótese de que a poesia contemporânea tende à iconicidade e mesmo da completa ilegibilidade como modo de apreensão estética de um mundo caótico. Porque não se constituem e nem podem ser lidos a partir das mesmas regras da lírica tradicional, os textos deliberadamente obliterados desses poetas resultam na transformação inequívoca dos métodos de criação e leitura, não obstante a resistência de certos ramos da crítica.
Poetry as erasure in Carlfriedrich Claus and Ana Hatherly
Keywords: Experimental Poetry; Concrete Poetry; Visual Poetry; Poetry Criticism; Theory of Poetry; Poesia Experimental; Poesia Concreta; Poesia Visual; Crítica de Poesia; Teoria da Poesia